The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/11782218221146391
|View full text |Cite
|
Sign up to set email alerts
|

Using SBIRT (Screen, Brief Intervention, and Referral Treatment) Training to Reduce the Stigmatization of Substance Use Disorders Among Students and Practitioners

Abstract: Negative attitudes and stigmatization of substance-using patients lead to treatment avoidance and poor physical and health outcomes. Research suggests that training in substance use disorders is a vital tool to abate negative attitudes among health workers. The present longitudinal study trained students and experienced practitioners from various disciplines on the evidence-based Screening, Brief Intervention, and Referral to Treatment (SBIRT) model. The study found significant improvements in the attitudes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Two studies found reductions in stigma, 34,47 whereas 1 study found no change 38 . In 3 studies that used multiple stigma scales or looked at stigma against multiple conditions, findings were mixed between SUD and stigma scales 30,35,36 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies found reductions in stigma, 34,47 whereas 1 study found no change 38 . In 3 studies that used multiple stigma scales or looked at stigma against multiple conditions, findings were mixed between SUD and stigma scales 30,35,36 …”
Section: Resultsmentioning
confidence: 99%
“…Perceived Dangerousness Scale (measures perceived level of threat the described individuals pose to themselves and others) ------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------ ---------------------------------------------------------------------------------------------------------------------------OUD 12 weeks Reduced - ------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------Mahmoud et al, 35 2018 Pre-post Nursing students (n = 49) AUD 12 weeks Reduced - --------------------------------------------------------------------------------------------------------------------------OUD 12 weeks Reduced PSAS (measures perceived stigma in society or knowledge of stereotypes) ----------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------Gomez et al, 30 2023…”
Section: Weeksmentioning
confidence: 95%
See 3 more Smart Citations